ABUSE OF A DOMINANT POSITION ON THE DIGITAL MARKETS – CASE META VS. BUNDESKARTELLAMT (EU and comparative law issues and challenges series (ECLIC), 2024)
During the previous years of the ECLIC conference series, the case of Facebook (Meta), which started at the German national competition authority Bundeskartellamt, was analysed by our (broader or narrower) author team, from different perspectives. At issue was primarily the question that links the areas of data protection and competition - and thus whether the use and linking of personal data from this social network and from third parties can be considered an abuse of a dominant position in light of the fact that the collection of this data is a condition for the use of the platform. The legal case was transferred from the administrative phase, to the German national court, which referred the case to the Court of the Justice of European union (hereafter also as “CJEU”) for a preliminary ruling. Advocate General Athanasios Rantos also submitted his opinion in the case, and the CJEU in its judgment of 04 July 2023, answered the questions referred for a preliminary ruling. By answering the questions referred for a preliminary ruling in case C-252/21, CJEU drawed conclusions both in relation to the principle of sincere cooperation under Article 4(3) TEU between the competent data protection and competition authorities, and in relation to the regulation of personal data and competition. From a methodological point of view, the analysis will focus in particular on the decision in the case (C-252/21), taking into account the findings presented in professional literature with emphasis on the abuse of dominant position. The aim of this paper is to select the most relevant generally applicable conclusions of the judgement of 04 July 2023 for the application of the abuse of dominance in the context of extensive data collection.